Volume function and Mahler measure of exact polynomials. (14th April 2021) - Guilloux, Antonin; Marché, Julien
Abstract : We study a class of two-variable polynomials called exact polynomials which contains A -polynomials of knot complements. The Mahler measure of these polynomials can be computed in terms of a volume function defined on the vanishing set of the polynomial. We prove that the local extrema of the volume function are on the two-dimensional torus and give a closed formula for the Mahler measure in terms of these extremal values. This formula shows that the Mahler measure of an irreducible and exact polynomial divided by π is greater than the amplitude of the volume function. We also prove a K-theoretic criterion for a polynomial to be a factor of an A -polynomial and give a topological interpretation of its Mahler measure.